Theft [large type] - Gurnah, Abdulrazak, 1948- (Random House Large Print Publishing, 2025)
At the turn of the twenty-first century, three young people come of age in Tanzania. Karim returns to his sleepy hometown after university in Dar es Salaam with a new swagger and sense of ambition. There he catches the eye of Fauzia, who sees in him a chance at escape from a smothering upbringing. When the two of them offer a haven to Badar, a poor boy still unsure if the future holds anything for him at all, they little imagine how deeply their fates will entwine and diverge. As rapidly accelerating global change reaches even their quiet corner of the world, bringing tourists, technology, and unexpected opportunities and perils, each arrives at a different understanding of what it means to take your fate into your own hands.